Interfacial Curvature in Confined Coculture Directs Stromal Cell Activity with Spatial Corralling of Pancreatic Cancer Cells. Issue 6 (22nd March 2021) - Nemec, Stephanie; Lam, Joey; Zhong, Jingxiao; Heu, Celine; Timpson, Paul; Li, Qing; Youkhana, Janet; Sharbeen, George; Phillips, Phoebe A.; Kilian, Kristopher A.
Abstract: Interfacial cues in the tumor microenvironment direct the activity and assembly of multiple cell types. Pancreatic cancer, along with breast and prostate cancers, is enriched with cancer‐associated fibroblasts (CAFs) that activate to coordinate the deposition of the extracellular matrix, which can comprise over 90% of the tumor mass. While it is clear that matrix underlies the severity of the disease, the relationship between stromal‐tumor cell assembly and cell‐matrix dynamics remains elusive. Micropatterned hydrogels deconstruct the interplay between matrix stiffness and geometric confinement, guiding heterotypic cell populations and matrix assembly in pancreatic cancer. Interfacial cues at the perimeter of microislands guide CAF migration and direct cancer cell assembly. Computational modeling shows curvature‐stress dependent cellular localization for cancer and CAFs in coculture. Regions of convex curvature enhance edge stress that activates a myofibroblast phenotype in the CAFs with migration and increased collagen I deposition, ultimately leading to a central "corralling" of cancer cells. Inhibiting mechanotransduction pathways decreases CAF activation and the associated corralling phenotype. Together, this work reveals how interfacial biophysical cues underpin aspects of stromal desmoplasia, a hallmark of disease severity and chemoresistance in the pancreatic, breast, and prostate cancers, thereby providing a tool to expand stroma‐targeting therapeutic strategies. Abstract : Cocultured pancreatic cancer and stromal cells are directed spatiotemporally by micro confinement on hydrogels where precisely patterned geometries direct cell segregation and collagen I assembly. Perimeter cues at the perimeter of microislands guide cancer‐associated fibroblasts to coral cancer cells to the interior, thereby providing a model of stromal desmoplasia, characteristic of pancreatic cancer in vivo.